Apportionment of the Pre‐Industrial to Present‐Day Climate Forcing by Methane Using UKESM1: The Role of the Cloud Radiative Effect. (20th October 2022) - O'Connor, Fiona M.; Johnson, Ben T.; Jamil, Omar; Andrews, Timothy; Mulcahy, Jane P.; Manners, James
Abstract: The Year 1850 to 2014 increase in methane from 808 to 1831 ppb leads to an effective radiative forcing (ERF) of 0.97 ± 0.04 W m −2 in the United Kingdom's Earth System Model, UKESM1. The direct methane contribution is 0.54 ± 0.04 W m −2 . It is better represented in UKESM1 than in its predecessor model HadGEM2 due to shortwave and longwave absorption improvements and the absence of an anomalous dust response in the UKESM1 simulations. An indirect ozone ERF of 0.13–0.20 W m −2 is due to the tropospheric ozone increase outweighing that of the stratospheric decrease. The indirect water vapor ERF of 0.02–0.07 W m −2 is consistent with previous estimates. The methane increase also leads to a cloud radiative effect of 0.12 ± 0.02 W m −2 from thermodynamic adjustments and aerosol‐cloud interactions (aci). Shortwave and longwave contributions of 0.23 and −0.35 W m −2 to the cloud forcing arise from radiative heating and stabilization of the upper troposphere, reducing convection and global cloud cover. The aerosol‐mediated contribution (0.28–0.30 W m −2 ) is due to changes in oxidants reducing new particle formation (−8%), shifting the aerosol size distribution toward fewer but larger particles. Cloud droplet number concentration decreases and cloud droplet effective radius increases. This reduction in the Twomey effect switches the cloud forcing sign (−0.14 to 0.12 W m −2 ) and is due to chemistry‐aerosol‐cloud coupling in UKESM1. Despite uncertainties in rapid adjustments and process representation in models, these results highlight the potential importance of chemistry‐aerosol‐cloud interactions and dynamical adjustments in climate forcing. Plain Language Summary: Methane is the second most important greenhouse gas after carbon dioxide. Methane is also chemically reactive in the atmosphere, and can cause changes in ozone, which is also a greenhouse gas. Methane can also affect the amount of water vapor (WV) in the atmosphere, where it too acts as a greenhouse gas. Aerosols, formed in the atmosphere through chemical processing, are also affected by methane. This study quantifies the impact of changes in methane concentration since the pre‐industrial period on the Earth's energy budget at the present day and examines the impact from methane itself, as well as the impact from the additional methane‐driven changes in ozone, WV, aerosols, and clouds. The biggest impact (∼55%) is from methane itself, and of the remaining impact on the Earth's energy budget from methane, most can be attributed to ozone and clouds. The contribution from clouds is partly driven by changes in aerosol properties and partly driven by heating and a reduction in cloud cover. The impact from WV is small and is consistent with previous estimates. This study highlights the potential importance of including chemistry‐aerosol‐cloud interactions when quantifying the effect of pre‐industrial to present‐day changes in atmospheric constituents on climate. Key Points: The direct radiative effect of methane in UKESM1 is consistent with line‐by‐line radiative transfer calculations The total methane effective radiative forcing (ERF) in UKESM1 includes an aerosol‐mediated cloud forcing due to changes in cloud activation The ERF also includes a dynamically driven cloud forcing from tropospheric warming and a reduction in cloud fraction